Rationalized inhibition of mixed lineage kinase 3 and CD70 enhances life span and antitumor efficacy of CD8+ T cells - Sandeep Kumar; Sunil Kumar Singh; Navin Viswakarma; Gautam Sondarva; Rakesh Sathish Nair; Periannan Sethupathi; Matthew Dorman; Subhash C Sinha; Kent Hoskins; Gregory Thatcher; Basabi Rana; Ajay Rana (Journal for ImmunoTherapy of Cancer)
Background The mitogen-activated protein kinases (MAPKs) are important for T cell survival and their effector function. Mixed lineage kinase 3 (MLK3) (MAP3K11) is an upstream regulator of MAP kinases and emerging as a potential candidate for targeted cancer therapy; yet, its role in T cell survival and effector function is not known.Methods T cell phenotypes, apoptosis and intracellular cytokine expressions were analyzed by flow cytometry. The apoptosis-associated gene expressions in CD8+CD38+ T cells were measured using RT2 PCR array. In vivo effect of combined blockade of MLK3 and CD70 was analyzed in 4T1 tumor model in immunocompetent mice. The serum level of tumor necrosis factor-α (TNFα) was quantified by enzyme-linked immunosorbent assay.Results We report that genetic loss or pharmacological inhibition of MLK3 induces CD70-TNFα-TNFRSF1a axis-mediated apoptosis in CD8+ T cells. The genetic loss of MLK3 decreases CD8+ T cell population, whereas CD4+ T cells are partially increased under basal condition. Moreover, the loss of MLK3 induces CD70-mediated apoptosis in CD8+ T cells but not in CD4+ T cells. Among the activated CD8+ T cell phenotypes, CD8+CD38+ T cell population shows more than five fold increase in apoptosis due to loss of MLK3, and the expression of TNFRSF1a is significantly higher in CD8+CD38+ T cells. In addition, we observed that CD70 is an upstream regulator of TNFα-TNFRSF1a axis and necessary for induction of apoptosis in CD8+ T cells. Importantly, blockade of CD70 attenuates apoptosis and enhances effector function of CD8+ T cells from MLK3−/− mice. In immune-competent breast cancer mouse model, pharmacological inhibition of MLK3 along with CD70 increased tumor infiltration of cytotoxic CD8+ T cells, leading to reduction in tumor burden largely via mitochondrial apoptosis.Conclusion Together, these results demonstrate that MLK3 plays an important role in CD8+ T cell survival and effector function and MLK3-CD70 axis could serve as a potential target in cancer.